Walk the line - Witherspoon, Reese, 1976-; Goodwin, Ginnifer; Patrick, Robert, 1958-; Phoenix, Joaquin; Fox 2000 Pictures; Tree/Line Films; Catfish Productions (1997- ) (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2006)
Traces Johnny Cash's childhood, including his distant father to his early attempts at a music career. At this point in his life he marries his girlfriend Vivian. During a tour with singer/musicians Elvis and Jerry Lee Lewis, he encounters singer June Carter. His love for her, and her rejection of him through the years, spurs him into drugs, drinking, and depression. June is a sassy spitfire singer whose charm breaks hearts and eventually becomes a sympathetic friend who tries to help Johnny get over her. A true love story of two country music stars.
Full screen presentation.
Originally released as a motion picture in 2005.
Director of photography, Phedon Papamichael ; art directors, John R. Jensen, Rob Simons ; editor, Michael McCusker ; music, T-Bone Burnett ; costume designer, Arianne Phillips ; production designer, David J. Bomba.
Joaquin Phoenix, Reese Witherspoon, Ginnifer Goodwin, Robert Patrick.
DVD, region 1; Dolby Digital 5.1 surround.
Closed captioned for the hearing impaired. Includes French and Spanish dubbed versions and subtitles in English and Spanish.
Keywords: Cash, Johnny -- Drama -- DVDs; Cash, June Carter, -- 1929-2003 -- Drama -- DVDs; Country musicians -- United States -- Drama -- DVDs; Country music -- Drama -- DVDs; Man-woman relationships -- Drama -- DVDs; Feature films; Musical films; Biographical films; Video recordings for the hearing impaired